Analisis Komunikasi Pariwisata Disbudpar Kota Tangerang dalam Event Pariwisata Festival Cisadane 2024 - Gilang Kurniawan; Faisal Tomi Saputra; Mochammad Mirza (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The Cisadane Festival is an annual event organised with the aim of preserving culture in Tangerang City.  This festival is one of the large and lively tourist agendas because there are various interesting events presented. Thus, it needs to be promoted to increase the number of tourist visits. This research aims to analyse and find out how the Tourism Communication of the Tangerang City Culture and Tourism Office in promoting the Cisadane Festival held in Tangerang City, as well as to examine the obstacles that exist in the promotion process carried out. This research uses the theory of integrated marketing communication, with the method used in this research is descriptive qualitative. The results showed that tourism communication used by Disbudpar Tangerang City in promoting the Cisadane Festival integrated the promotion mix. This can be seen from the utilisation of various types of media: print media such as Live magazine and Kota Benteng newspaper, outdoor media such as banners and billboards, and electronic media which includes online media coverage and social media content. Barriers to promotional activities are due to marketing budget factors, urgent event readiness, and the lack of optimisation of the Tangerang Live service application.